MANIA INDUCED BY STEROID-ADULTERATED HERBAL MEDICINE: A CASE REPORT - Gan, Lydia Lay Yen; Woon, Luke Sy-cherng; Zawawi, Maria Ulfaahmad; Midin, Marhani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Traditional herbal medicines are generally perceived as natural and safe. Nonetheless, adulteration of such complementary products, including Chinese Proprietary Medicines with undeclared drugs, notably steroids, is a recognized problem. While there are many accounts of Cushing's syndrome due to steroid content in traditional medicines, psychiatric complications caused by the similar insults are not reported throughout the literature. We report a case of acute mania after the short-term use of steroid-adulterated herbal product in a previously healthy young male. It shows that psychiatric complications can occur in such a scenario without the physical and metabolic features of Cushing's syndrome, and pharmacodynamic interaction between the herbal ingredient and adulterant is a possible factor. The case also highlights the need for awareness of culturally influenced health product consumption and its potential effects on clinical conditions, as well as the important role of a robust surveillance system for such products.